Implementing Empathy-Based Learning To Reduce Early Childhood Aggressive Behavior At KB Riyadussolihin - Imas Masitoh; Evi Siti Sonia; Gina Raudatul Janah; Ai Ratika (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Background: Aggressive behavior in early childhood has become an increasing concern because it negatively affects children's social-emotional development and may be intensified by exposure to inappropriate emotional experiences in the digital era. Developing empathy through classroom learning is considered a promising strategy for preventing aggressive behavior. Objective: This study aimed to examine the effect of empathy-based learning on reducing aggressive behavior among early childhood children at KB Riyadussolihin, Cianjur Regency. Method: This study employed a quantitative quasi-experimental design using a one-group pretest-posttest approach. Fifteen children were selected through purposive sampling from a population of 21 children based on the highest aggressive behavior scores. Data were collected using structured observation sheets measuring physical, verbal, and relational aggression and were analyzed using descriptive statistics and a paired-samples t-test with SPSS. Results: The findings revealed a statistically significant difference between pretest and posttest scores (p < 0.001), indicating that empathy-based learning significantly influenced children's aggressive behavior. The intervention produced a very large effect size (Cohen's d = −1.512). Although the posttest mean score increased, this finding should be interpreted cautiously because the observation instrument demonstrated relatively low reliability. Novelty: This study provides empirical evidence supporting empathy-based learning as a structured classroom intervention for addressing aggressive behavior in early childhood. Conclusion: Empathy-based learning shows strong potential to promote positive behavioral change and should be integrated into early childhood education through interactive activities and collaboration between teachers and parents.